تفسیر شعراوی کا منہج واسلوب: Methodology Of "Tafsir al-Sha'ravi" - Azmi, Muhammad Ilyas; Shams, Dr. Shamsur Rahman (Al-Irfan, 2023)
The holy Quran is the eternal charter of guidance and code of conduct for the people So man should pay attention to the holy Qura'an and understand its teachings through the path of the companions of Holy Prophet Muhammad (P.B.U.H), who were the eye witness of the revelation of Qura'an and we're successful in life practicing upon the Doctrine of Qura'an. Since then, a successful group has been there who not only tries to comprehend Qura'an but struggled to explain the true meanings of Qura'an to their fellow beings. One of these strives is the "Tafsir al-Sha'ravi". It counts in golden chain of tafasir and written by "Sh. Mohammad Metwalli al- Sha'ravi". The common Muslims in general and the Muslim youth in particular must be well aware of the comprehensive methodology of the interpreter.In this article the important and distinctive features of "Tafsir al-Sha'ravi" have been described analytically.